2006
DOI: 10.1093/carcin/bgl025
|View full text |Cite
|
Sign up to set email alerts
|

Dietary resistant starch type 3 prevents tumor induction by 1,2-dimethylhydrazine and alters proliferation, apoptosis and dedifferentiation in rat colon

Abstract: Some epidemiological and experimental studies suggest that consumption of resistant starch is preventive against colon cancer. Resistant starch leads to a fermentation-mediated increase in the formation of short-chain fatty acids, with a particularly high butyrate fraction in large bowel. Butyrate is considered to be protective against colon cancer because it causes growth arrest and apoptosis and regulates expression of proteins involved in cellular dedifferentiation in various tumor cell lines in culture. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 71 publications
6
80
0
6
Order By: Relevance
“…31 Few in vivo studies examining tumorigenesis with intervention by RS or other fermentable substrates have investigated the colonic apoptotic response at this late time point. Bauer-Marinovic et al 8 however did observe a significant increase in apoptosis in rats fed hydrothermally treated RS 3 . In this particular study apoptosis was measured in the colon of rats that had received an intensive and prolonged carcinogen schedule, namely 20 s.c. injections of DMH where the rats were killed one week after the last DMH injection.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…31 Few in vivo studies examining tumorigenesis with intervention by RS or other fermentable substrates have investigated the colonic apoptotic response at this late time point. Bauer-Marinovic et al 8 however did observe a significant increase in apoptosis in rats fed hydrothermally treated RS 3 . In this particular study apoptosis was measured in the colon of rats that had received an intensive and prolonged carcinogen schedule, namely 20 s.c. injections of DMH where the rats were killed one week after the last DMH injection.…”
Section: Discussionmentioning
confidence: 85%
“…These are summarised in Young et al 4 and the results are conflicting. More recently hydrothermally treated RS 3 protected against dimethylhydrazine (DMH)-induced colon carcinogenesis 8 and high amylose maize starch protected against AOM-induced colon cancer. 9 There are several explanations for the varying results between the reported studies: the different carcinogen protocols (dose and duration), differences in starch type, feeding regimens, lack of effect on fermentation parameters and the comparative control diet.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the study by Wacker et al (64) which administered the largest dose of RS (up to 59·7 g /d). In contrast, a number of studies have reported reduced cell proliferation in the colorectum of individuals with neoplasia (25,26) . Importantly, we have also shown that supplementation of CRC patients with a 1:1 blend of Novelose 240 and Novelose 330 (RS types 2 and 3) reduced the proportion of mitotic cells in the top half of the crypt (65) .…”
Section: The Effects Of Resistant Starch and Butyrate On Colonic Crypmentioning
confidence: 96%
“…While some studies have indicated a chemoprotective effect of RS, others have reported no effect and some have observed adverse effects. In rats treated with 1,2-dimethylhydrazine dihydrochloride (DMH; a carcinogen used widely in experimental studies of CRC formation), incidence of tumours was reduced when the animals were fed Novelose 330 (a type 3 RS) compared with those fed a standard diet (25) . High-amylose maize starch (HAMS; a type 2 RS) has also been shown to reduce incidence and the number of adenocarcinomas in rats when the HAMS diet was provided for 4 weeks prior to injection with the carcinogen azoxymethane (26) .…”
Section: The Effects Of Resistant Starch On Colorectal Carcinogenesismentioning
confidence: 99%
“…All of these components are primarily in aqueous-alcohol extracts of dry beans (37)(38)(39)(40). Resistant starches and nonstarch polysaccharides are cancer-preventive components (41)(42)(43), which are primarily insoluble residues from aqueous-alcohol extracts of dry beans. Cancer-preventive components in dry beans could act either alone or in combination.…”
Section: Introductionmentioning
confidence: 99%